Atividade antitubercular de indóis como candidatos a fármacos para o tratamento da tuberculose - Neves, Christiano Ev (2023)
Emerging viral and bacterial infections continue to pose a major threat to global public health. Over the past 30 years, the emergence of more than 30 new infectious diseases has been described. That number corresponds to about 60% of all human infectious diseases known so far. Among the numerous diseases caused by bacteria, tuberculosis (TB) is an infectious disease contracted through contact with Mycobacterium tuberculosis (Mtb), its main etiological agent, which mainly attacks the lungs. Its form of transmission is mainly respiratory, when particles from the environment are inhaled, in the form of aerosols, containing the bacillus. Even with an adequate diagnosis and pharmacological treatment available, estimates show that TB is one of the leading causes of death due to a single infectious agent (behind only COVID19 and ahead of HIV infection) and it is among the main causes of death in the world considering all diseases (13th cause of death). Given this scenario, the search for drugs that will update the treatment regimen is urgent and the use of chemical structures from the most different classes is the subject of several lines of research. Among the structures, the indole heterocyclic was used as the core of this work in order to evaluate its antitubercular action. The results obtained were able to list the compound 5-Fluoroindole (5-FI) as a promising structure, having the same biological action against the laboratory strain H37Rv (4.7μM) as in strains containing resistance to first-line drugs used in the disease treatment. It was also possible to list the structure regarding its viability and low cytotoxicity in two cell lines, Vero and HepG2 and selectivity, stability in different hydrogen-ionic concentrations that mimic physiological pH, establish its high permeability by the PAMPA assay (2.4x10-6 cm/s). Such assays made it possible to cross the barrier from in vitro to in vivo assays, making it possible to obtain results in both contexts not only because of the capacity of the salt in the form of hydrochloride to be available in the systemic circulation as the compound was able to reduce the Mtb load at a concentration of 200 μM/Kg after submitting it to a 21-day infection murine model with the bacillus in its active form. The sum of data obtained demonstrate the possibility of the compound 5-FI.HCl being used as a drug candidate in the treatment of Tuberculosis based on its biological activity both in the laboratory strain and in strains that contain a phenotype of resistance to drugs used in the treatment of TB . The structure showed selectivity for the bacillus that caused the disease and was able to maintain biological activity when crossing the barrier from in vitro to in vivo experimentation.